Experimental and theoretical study of Matricaria recutita chamomile extract as corrosion inhibitor for steel in neutral chloride media. Issue 3 (25th May 2018) - Nasr, Khaoula; Fedel, Michele; Essalah, Khaled; Deflorian, Flavio; Souissi, Nebil
Abstract : Purpose: This study aims to investigate the inhibition performance of an aqueous extract of Matricaria recutita chamomile on the corrosion of S235JR steel in 0.5 M NaCl by using electrochemical impedance spectroscopy (EIS) and polarization measurements. Design/methodology/approach: The inhibition performance was investigated using EIS and polarization measurements. Surface analysis demonstrates the presence of a protective layer on the steel surface in the presence of the extract. Quantum chemical parameters calculated for the molecules contained in the aqueous extract are interpreted to predict the corrosion inhibition efficiency of the considered extract. Findings: The inhibition efficiency of chamomile aqueous extract for S235JR steel increases with increasing amounts of plant concentration and with an increase in the immersion time. The optimal inhibition efficiency of chamomile extract, 98.90 per cent, was achieved for S235JR steel when immersed in 15 per cent v/v of extract concentration for 2 h. The surface analysis in the absence and presence of the chamomile extract confirmed the formation of a protective layer on steel surface. The quantum chemical calculations allowed to explain the great inhibition efficiency values by interpreting the calculated quantum parameters. Originality/value: This is the first study carrying out an experimental and theoretical investigation on M. recutita chamomile as a green corrosion inhibitor, with interesting potential industrial applications.